Trademark Protection and Territoriality Challenges in a Global Economy - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2014)
As the modern business world becomes increasingly decentralized and globally focused, traditional interpretations and applications of trademark protection law are facing greater and greater challenges. This is particularly true regarding the principle of trademark territoriality, which holds that trademark rights are bound by the laws of individual nations. This timely volume offers expert analyses of the challenges facing crucial aspects of trademark law from some of the most prominent scholars in the field.